Oppositional voices : women as writers and translators of literature in the English Renaissance - Κροντήρη, Τίνα, 1950- (Routledge, 1992)
Oppositional Voices is a study of women writers in the late Elizabethan period. Until the early 1980s it was generally assumed that women did not write any books during the Renaissance. Virginia Woolf wondered why, 'no woman wrote a word of that extraordinary literature when every other man, it seemed, was capable of song or sonnet. The women discussed in this book did write something of that 'extraordinary literature'. Ignoring Renaissance society's injunction that women should confine themselves to religious compositions, they wrote and translated poetry, drama and romantic fiction. They even voiced opposition to certain oppressive ideas and stereotypes. Yet, as this study suggests, what these authors finally say depends greatly on the fact that they were women writing in a culture inimical to female creative activity. 0ppositional Voices shows how gender ideology intertwined with economics and social class, as well as with literary and linguistic conventions, to shape women's writing of the period.